Relationship of Pneumocystis jiroveci Humoral Immunity to Prevention of Colonization and Chronic Obstructive Pulmonary Disease in a Primate Model of HIV Infection - Kling, Heather M. (American Society for Microbiology (ASM), 2010)
Pulmonary colonization by the opportunistic pathogen Pneumocystis jiroveci is common in HIV(+) subjects and has been associated with development of chronic obstructive pulmonary disease (COPD). Host and environmental factors associated with colonization susceptibility are undefined. Using a simian-human immunodeficiency virus (SHIV) model of HIV infection, the immunologic parameters associated with natural Pneumocystis jiroveci transmission were evaluated. SHIV-infected macaques were exposed to P. jiroveci by cohousing with immunosuppressed, P. jiroveci-colonized macaques in two independent experiments. Serial plasma and bronchoalveolar lavage (BAL) fluid samples were examined for changes in antibody titers to recombinant Pneumocystis-kexin protein (KEX1) and evidence of Pneumocystis colonization by nested PCR of BAL fluid. In experiment 1, 10 of 14 monkeys became Pneumocystis colonized (Pc(+)) by 8 weeks post-SHIV infection, while 4 animals remained Pneumocystis colonization negative (Pc(−)) throughout the study. In experiment 2, 11 of 17 animals became Pneumocystis colonized by 16 weeks post-SHIV infection, while 6 monkeys remained Pc(−). Baseline plasma KEX1-IgG titers were significantly higher in monkeys that remained Pc(−), compared to Pc(+) monkeys, in experiments 1 (P = 0.013) and 2 (P = 0.022). Pc(−) monkeys had greater percentages of Pneumocystis-specific memory B cells after SHIV infection compared to Pc(+) monkeys (P = 0.037). After SHIV infection, Pc(+) monkeys developed progressive obstructive pulmonary disease, whereas Pc(−) monkeys maintained normal lung function throughout the study. These results demonstrate a correlation between the KEX1 humoral response and the prevention of Pneumocystis colonization and obstructive lung disease in the SHIV model. In addition, these results indicate that an effective Pneumocystis-specific memory B-cell response is maintained despite progressive loss of CD4(+) T cells during SHIV infection.